1988
DOI: 10.1017/s0022112088000102
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of particle dispersion in an axisymmetric jet

Abstract: Particle dispersion in an axisymmetric jet is analysed numerically by following particle trajectories in a jet flow simulated by discrete vortex rings. Important global and local flow quantities reported in experimental measurements are successfully simulated by this method.The particle dispersion results demonstrate that the extent of particle dispersion depends strongly on γτ, the ratio of particle aerodynamic response time to the characteristic time of the jet flow. Particles with relatively small γτ values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(69 citation statements)
references
References 12 publications
6
61
0
2
Order By: Relevance
“…b was set to 0.35 times the initial distance of vortices located at the splitter plate following initial tests. This ratio is in agreement with Chung & Troutt (1988). The inflow boundary conditions for the generation of a free shear flow were satisfied by adding vortices on the virtual splitter plate with an initial distance of 1.75 mm and releasing them at the end of the plate.…”
Section: Physical Interpretation Of the Model Equationsupporting
confidence: 78%
See 1 more Smart Citation
“…b was set to 0.35 times the initial distance of vortices located at the splitter plate following initial tests. This ratio is in agreement with Chung & Troutt (1988). The inflow boundary conditions for the generation of a free shear flow were satisfied by adding vortices on the virtual splitter plate with an initial distance of 1.75 mm and releasing them at the end of the plate.…”
Section: Physical Interpretation Of the Model Equationsupporting
confidence: 78%
“…Chorin (1973) reinvented the method by using vortex blobs and Leonard (1980Leonard ( , 1985 and Sarpkaya (1989) compiled reviews of the method and a more mathematical treatment can be found in Cottet & Koumoutsakos (2000). Chung & Troutt (1988) For St between 0.1 and 10, the calculations showed that particles which were on one side of the cylinder wake could cross the centre line and diffuse to the symmetrical side of the flow and further (up to radial distances of 2 cylinder diameters) due to interaction with fluid vortices. Direct numerical simulation was used by Ling et al (1998) to study three-dimensional dispersion in a particle-laden shear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Particle density is in all cases large compared to fluid density. Particle momentum balance equation as discussed by Maxey and Riley [37] was simplified according to previous works [11,33] neglecting virtual mass, pressure gradient force, and Basset force. The only forces considered were inertia and drag which was computed according to the non-linear model as in [54].…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In many environmental and industrial flow processes small inertial particles are entrained into eddies and vortices [9,13] and typically transported over significant distances before being expelled or falling out as the flow structures impact on rigid surfaces or obstacles placed in the flow. Because of the general properties of vortical flows, similar structures occur in many types of turbulent and unsteady flows.…”
Section: Introductionmentioning
confidence: 99%